EVALUATION OF THE THERAPEUTIC EFFICACY OF PRECONDITIONED MESENCHYMAL STEM CELLS IN A MOUSE MODEL OF PSORIASIS: PASI AND HISTOLOGICAL ANALYSIS - Dairov, A.K.; Issabekova , A.S.; Ogay , V.B. (Eurasian Journal of Applied Biotechnology, 2025)
Psoriasis is a common immune-mediated inflammatory skin disease that affects 2-4% of the world’s population and about 2.5% of the population of Kazakhstan. Mesenchymal stem cells (MSCs) are of particular interest for the treatment of psoriasis due to their strong immunomodulatory and regenerative potential. One of the strategies to increase the therapeutic efficacy of MSCs is their preconditioning with proinflammatory cytokines, which improves their survival and immunoregulatory properties. Aim of the study: Evaluation of the therapeutic effect of human umbilical cord blood mesenchymal stem cells (hUCB-MSCs) preconditioned with combinations of the cytokines interleukin (IL)-17A, IL-22, and tumor necrosis factor-alpha (TNF-α) in a mouse model of imiquimod (IMQ)-induced psoriasis-like skin inflammation. Results: Assessment of skin inflammation severity using the PASI score, along with subsequent histological analysis, demonstrated that both intact and preconditioned hUCB-MSCs effectively reduced IMQ-induced skin inflammation. In addition, hUCB-MSCs preconditioned with a combination of IL-22 and TNF-α significantly reduced erythema and scaling, while hUCB-MSCs preconditioned with a combination of IL-17A, IL-22 and TNF-α significantly reduced skin thickening. Conclusion: Preconditioned hUCB-MSCs exhibit a pronounced anti-inflammatory potential, confirming their therapeutic promise for the treatment of psoriasis.